Action plan for IELTS - "Jakeman, Vanessa" (Cambridge, 2012)
No time before your IELTS test? You need Action Plan for IELTS. Designed for use in the last few weeks before the test, Action Plan for IELTS increases your confidence and helps you maximise your score. It includes examples of all the task types and provides test guidance and practice for each one. The 'Action Plan' gives tips and advice to help you target each section of the test effectively (Listening, Reading, Writing and Speaking). Last-minute preparation Action Plan for IELTS familiarises you quickly with the test. It covers each part of each paper in short units to help you improve your test technique and maximise your score. Practice test Action Plan for IELTS has a complete IELTS practice test for times practice under test conditions. Self-study guide Action Plan for IELTS has a full answer key, including model answers and recording scripts. Action Plan for IELTS is available in two separate editions: Academic Module and General Training Module.
Keywords: International English Language Testing System